Incorporating spiritual wisdom: A paradigm shift in management education insights from the Bhagavad Gita - Saxena, Karunesh and Sharma, Mukesh K. (University News)
In the contemporary business landscape, there is a growing recognition among leaders about the importance of sustainable management practices and ethical considerations in management education. Leaders are honing their management skills to integrate ethical considerations into decision-making, ensuring that their organizations prioritize sustainability, social responsibility, and ethical business practices (Bentley 2023). Reproduced